SmUDo (Smart Unit-Dose): Redefining efficiency, quality, and staffing strategies for optimized processes - Jana Gerstmeier; Saskia Herrmann; Annika Demuth; Natalie Vuong; Olaf Kannt; Dominic Fenske (PLoS ONE, 2026)
Background The implementation of unit-dose dispensing systems (UDDS) in hospital pharmacies represents a major milestone in the digital transformation of medication therapy management, operational efficiency, and improving patient safety. However, the absence of standardized metrics for workforce planning and cost assessment has limited widespread adoption. This gap makes it increasingly challenging for healthcare stakeholders to optimize the allocation of limited medical and financial resources. Methods Using data from a 1,800-bed tertiary care hospital with 1,680 UDDS beds (2021–2024), this study establishes benchmarks for staffing requirements and associated costs. The following key performance metrics were analyzed: task-specific work times, unit-dose machine utilization, and productivity indicators such as blistered tablet output and blister bag production per full-time equivalent (FTE). Results The findings indicate a staffing benchmark of 0.45 FTE per 100 UDDS-covered hospital beds to support both implementation and routine operations. Workforce efficiency improved significantly, with the number of FTEs per 1 million blistered tablets decreasing from 3.2 in 2021 to 1.7 in 2024. Concurrently, the cost per blister bag improved from €0.55 in 2021 to €0.22 in 2024, well within the optimal unit target price range of €0.20-€0.25; blistered tablet production tripled, rising from 1.5x10 6 to 4.7x10 6 between 2021 and 2024 respectively. A gold standard of 1 FTE per 10,000 cases was established to optimize staffing and operational workflows. The sharp decline in FTE per 1 million requirements from 5.45 to 2.29 underscores the pivotal role of experienced clinical pharmacists in ensuring safe, accurate, and resource-optimized prescription validation. Conclusion The proposed benchmarks provide practical guidance for improving UDDS productivity, optimizing resource allocation, and strengthening workforce management. Our findings provide a framework that supports continuous UDDS improvement in hospital pharmacy operations and evidence-based decision-making for key stakeholders. By establishing clear UDDS benchmarks, this study supports cost-efficient UDDS operations while providing surrogate indicators of patient safety and clinical quality.